Environmental assessment of applicability of mineral-organic composite for landfill area rehabilitation - Mizerna Kamila; Król Anna; Mróz Adrian (E3S Web of Conferences, 2017)
This paper undertakes an assessment of the impact of a mineral-organic composite on the environment as well as the potential for its application for land rehabilitation purposes. The analysis involves the release of the leachable contaminations from the material subjected to testing. This material was formed by a composite manufactured on the basis of communal bottom ash and stabilized sewage sludge. The sludge resulting from wastewater treatment was subjected to stabilization and dehydration in waste pounds at the phase of pre-watering until 20% of dry mass is obtained. Subsequently, they were mixed with bottom ash, which was obtained from selective waste collection, in a 1:1 mass ratio. The analysis involved the leaching of inorganic contaminants in the form of heavy metals, sulphates (VI), chlorides, and fluorides as well as organic compounds in the form of organic carbon solution under the effect of leachant with a various level of pH. The analysed components were characterized by various leaching behaviour depending on the leachant pH. On the basis of the results, it was able to assess the potential hazard posed by the examined material on the environment as a consequence of its application for landfill area rehabilitation.